Anti-Oxidant and Vitamin C Activity Test of Horseganik Clay Mask Products, Sumbawa Horse Milk - Munandar, Imam (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2024)
The growth of the cosmetics market in Indonesia is also projected to increase by 7% in 2021 (Databoks, 2021).